Assessment of Causality, Severity and Seriousness of Adverse Event Following Immunization in Iraq: A Retrospective Study Based on Iraqi - K. Abd, Ahmad; J. Kadhim, Dheyaa; M. Younus, Manal (Iraqi Journal of Pharmaceutical Sciences, 2019)
Immunization is one of the most cost-effective and successful public health applications. The results of immunization are difficult to see as the incidence of disease occurrence is low while adverse effects following the immunization are noticeable, particularly if the vaccine was given to apparently healthy person. High safety expectations of population regarding the vaccines so they are more prone to hesitancy regarding presence of even small risk of adverse events which may lead to loss of public trust to the vaccination programs. Vaccine safety monitoring is needed as they now are administered to the general population and also available to special categories such as pregnant women and patients with different diseases whom not subjected to clinical trials as well as incorrect administration rout and presence of rare or delayed onset adverse events make the presence of surveillance system necessary. The aim of the current study was to measure the distribution, percentage, and frequency of adverse reactions related to vaccines administration in Iraq and to assess the causality, severity, seriousness of these adverse reactions. This study is a retrospective descriptive study for surveillance of vaccine safety conducted using Iraqi pharmacovigilance center database from 2014 till the end of 2018 . 2116 Adverse events were included and outcomes , severity , seriousness , and causality of adverse events were assessed. Majority of adverse events following immunization cases (90.97%) were mild, non serious (94.47%) and recovered (94.23%). Most reports were for general disorders and administration site conditions and the majority were for elevated body temperature and injection site reactions .